Multiwalled carbon nanotube based aromatic volatile organic compound sensor: sensitivity enhancement through 1-hexadecanethiol functionalisation - Bohli, Nadra; Belkilani, Meryem; Casanova-Chafer, Juan; Llobet, Eduard; Abdelghani, Adnane (Beilstein Journal of Nanotechnology, 2019)
Aromatic volatile organic compound (VOC) sensors are attracting growing interest as a response to the pressing market need for sensitive, fast response, low power consumption and stable sensors. Benzene and toluene detection is subject to several potential applications such as air monitoring in chemical industries or even biosensing of human breath. In this work, we report the fabrication of a room temperature toluene and benzene sensor based on multiwall carbon nanotubes (MWCNTs) decorated with gold nanoparticles and functionalised with a long-chain thiol self-assembled monolayer, 1-hexadecanethiol (HDT). High-resolution transmission electron microscopy (HRTEM) and Fourier transform infrared spectroscopy (FTIR) were performed to characterize the gold nanoparticle decoration and to examine the thiol monolayer bonding to the MWCNTs. The detection of aromatic vapours using Au-MWCNT and HDT/Au-MWCNT sensors down to the ppm range shows that the presence of the self-assembled layer increases the sensitivity (up to 17 times), selectivity and improves the response dynamics of the sensors.
Keywords: gold-decorated MWCNTs; multiwall carbon nanotubes (MWCNTs); self-assembled monolayers (SAMs); sensitivity; selectivity; vapour sensor